2010
DOI: 10.1007/s10552-010-9598-2
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of HPV DNA and cytology testing in 50,159 women in the routine Mexican Social Security Program

Abstract: Population-based programs using HR-HPV testing can improve cervical cancer prevention and control in Mexican and other populations where cytological screening is inadequate for detecting precursors of cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 39 publications
3
25
0
1
Order By: Relevance
“…This same pattern is seen in the Guanacaste cohort in Costa Rica [21] and in the previous Mexican study for HPV16, but not for HPV18 [11]. Overall, point estimates of HPV16/18 prevalence appear higher in other study populations throughout Latin America [9, 21, 23, 31], but due to different study designs, it is difficult to draw conclusions concerning the comparative burden of infections.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This same pattern is seen in the Guanacaste cohort in Costa Rica [21] and in the previous Mexican study for HPV16, but not for HPV18 [11]. Overall, point estimates of HPV16/18 prevalence appear higher in other study populations throughout Latin America [9, 21, 23, 31], but due to different study designs, it is difficult to draw conclusions concerning the comparative burden of infections.…”
Section: Discussionsupporting
confidence: 70%
“…While cytology seems to be an obvious triage option given the existing infrastructure, we are also trying alternatives because of the difficulty of maintaining high-quality cytology in Mexico [9]. One potentially important option for the triage of hrHPV positive women would be to identify those positive for HPV16 and HPV18 for further evaluation and diagnostic confirmation.…”
Section: Introductionmentioning
confidence: 99%
“…18 Moreover, it was reported that PAP combined with HPV test increases the capability to identify cervical cancer 13,19,20 .…”
Section: Concurrent Infectionsmentioning
confidence: 99%
“…13 In this study, we determined HPV prevalence in 159,288 women in Michoacán State and HPV genotype in 45 samples from the Women's Hospital in Morelia, Michoacán.…”
Section: Introductionmentioning
confidence: 99%
“…For the catch-up campaign for 14–15 year old boys the 3-dose coverage was assumed to be 72% equally split between 2013 and 2014. While the actual efficacy of the vaccine at preventing transmission is still unknown, we assumed the lower bounds of 80% for women [20,21] and 50% for men based on data from the clinical trials on efficacy against persistent infection [22]. The same trials showed that the efficacy could also be as high as 90% in women and 80% in men, but we consider the worst case scenario in this paper.…”
Section: Methodsmentioning
confidence: 99%